Effect of Calcium Level in Feed on Blood Profile of Broiler Chicken - Modesta Salu; Charles Venirius Lisnahan; Oktovianus R. Nahak (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This study aims to determine the effect of calcium supplementation in feed on the blood profile of broilers chickens. This research was conducted in a broiler chicken coop, owned by breeders in Sasi Village, Kefamenanu City District, North Central East District. This research was conducted from July to August 2020. This study used 96 broilers. The method used in this was a completely randomized design consisting of 4 replications and 4 treatments. The treatments given were T0 (control diet), T1 (calcium supplementation 1,00 %), T2 (calcium supplementation 1,50 %), T3 (calcium supplementation 2,00 %). The variables observed in this study were the content of erythrocytes, hemoglobin, and blood leucocytes. The data obtained were analyzed using analysis of variance. Analysis of variance showed that the treatment had no significant effect on erythrocytes, hemoglobin, and leucocytes of broiler chickens. It was concluded that the addition of calcium in feed at different levels did not increase the content of erythrocytes, hemoglobin, and leucocytes of broiler chickens aged 6 weeks.